A Quick Identification Method of AC andDC Power Supply Systems for Electric Locomotive - ZOU Donghai; GAN Weiwei; GUO Wei; LIN Zhenjun; HUANG Hao; ZHOU Yang; CHEN Ke (Kongzhi Yu Xinxi Jishu)
In railway power system, where AC and DC systems co-exist, electric locomotives need to quickly change the working mode of traction system in accordance with the power supply systems. At present, the common power supply system identification methods mainly include manual identification and network voltage detection device identification. Taking the power supply system with AC 25 kV and DC 3 kV as an example, this paper proposes a method to quickly identify AC and DC power supply systems of electric locomotive, which overcomes the issues such as identification error and time consuming of manual identification, the impact of communication interruption and high cost of network pressure detection device identification. This method constructs an AC grid voltage transformer and a voltage sensor into a topology that can collect grid voltage signals, and the identification algorithm can quickly identify the current power supply system according to the different signal characteristics of AC and DC power supply systems. Experimental results show that the electric locomotive using this method can accurately identify the power supply system and complete the working mode switch of the traction system within 100 ms, and this method has more economical and safer advantages compared with the traditional ones.